Reconstruction of the seasonal cycle of air-sea CO2 fluxes in the Strait of Gibraltar - de la Paz, Mercedes; Huertas, Emma M.; Padín, Xose Antonio; Gónzalez-Dávila, Melchor; Santana-Casiano, Magdalena; Forja, Jesús M.; Orbi, Abdellatif; Pérez, Fiz F.; Ríos, Aida F. (Marine Chemistry, 2011)
The present study reports and discusses water surface fCO2 measurements from 36 cruises in the Strait of Gibraltar made over an eleven-year period (1997 to 2009). Underway measurements of sea surface CO2 fugacity (fCO2sw), sea surface temperature (SST) and sea surface salinity (SSS) compiled during the cruises were analysed and integrated into a single database which provided the resolution/sensitivity required for an examination of the seasonal variability of the fCO2sw; these data allowed the reconstruction of the climatological seasonal cycle for the year 2005. The seasonal cycle of both SST and SSS was found to be within the range of the thermohaline signature of the North Atlantic Surface Water, which is the main water mass that flows into the Mediterranean Sea through the Strait of Gibraltar at the surface. The seasonal distribution of fCO22005 was characterised by a monthly minimum value of 334 ± 12 μatm in May, followed by a gradual increase to a maximum of 385 μatm during late summer, due to the warming of surface waters. The spatial variability of fCO2sw observed in the area also indicated that superimposed phenomena, occurring at scales other than seasonal, could affect the dissolved CO2 distribution. In particular, intense vertical mixing processes generated by internal waves in this region may have an impact on the surface fCO2sw on a tidal scale. Seasonal CO2 cycle dynamics indicated that the surface waters of the Strait of Gibraltar acted as an atmospheric CO2 source during summer and autumn and a CO2 sink during winter and spring. When these sink/source strengths are integrated on an annual basis, the Strait of Gibraltar was close to equilibrium with atmospheric CO2, resulting in a neutral atmosphere-ocean exchange (− 0.06 ± 0.12 mol C m− 2 yr− 1). 162 155 2,126 3,074 Q1 Q1 SCIE